Hubungan Manajemen Perpustakaan dan Peran Guru Terhadap Minat Baca Siswa di MAN 1 Pangandaran - Nova Merisa; Irpan Ilmi; Predi Supriadi; Anza Sugiarti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
A high interest in reading will affect a person's skills. Each skill is interrelated with each other and is related to the processes that underlie language skills. Seeing the importance of reading interest, efforts are needed to foster reading interest in a person. Therefore, the school library must be utilized as much as possible as an information resource center and a center for fun educational recreation facilities for its users, especially students, so that it is hoped that the school library can foster students' interest and love of reading. The purpose of this study is how library management, how the role of teachers on reading interest, how student reading interest, is there a relationship between library management and student reading interest, is there a relationship between the role of teachers on student reading interest, is there a relationship between library management and the role of teachers on student reading interest. This study only focuses on the relationship between library management and the role of teachers on student reading interest. The type of approach used is qualitative method with naturalistic research method because the research is conducted in natural conditions (natural environment). The relationship between the library and the role of the teacher is quite good, while the role of the teacher in improving student reading is very instrumental. Therefore, all teachers must understand the role of what it takes to improve student skills at MAN 1 Pangandaran. This research is expected to contribute to related parties such as principals, teachers, committee administrators to add insight or knowledge about the importance of library management and teacher motivation in fostering students' interest in reading.